Pengaruh Consumer Trust dan Expectation Terhadap Online Repurchase Intention Melalui Customer Satisfaction Pada Situs Jual Beli Online Bukalapak di Kota Yogyakarta - Tri Wibowo (JURNAL EKOBIS DEWANTARA, 2018)
This study was conducted to determine the influence of consumer trust and expectation in online repurchase intention through customer satisfaction on the online sale site Bukalapak in Yogyakarta . Research location in Yogyakarta. The population of this research is the customer who stayed in Yogyakarta. Sample of 100 respondents were taken using accidental sampling techniques and methods of data collection using questionnaires. Analysis of the data used is descriptive analysis, multiple regression analysis, and path analysis. The results showed that consumer trust significantly influence customer satisfaction; consumer trust significantly influence online repurchase intention; and customer satisfaction significantly influence online repurchase intention.